2018
DOI: 10.3390/socsci7100197
|View full text |Cite
|
Sign up to set email alerts
|

When in Rome, Feel as the Romans Feel: An Emotional Model of Organizational Socialization

Abstract: Organizational socialization literature has long emphasized learning organizational culture upon entry. However, most previous socialization studies have largely focused on learning job skills, such as role clarity and task mastery. Focusing on emotional culture, the author provides a review about the roles of emotions in an organizational socialization context. Further, drawing upon the organizational socialization and emotion literature, the author builds a theoretical model, an emotional model of organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 142 publications
0
9
0
Order By: Relevance
“…role complexity, pressure) that can interfere with individuals’ learning ability. A second, more normative, perspective focuses on the extent to which newcomers learn about what emotions are acceptable in their new organization and how to adjust their own emotions to create a better fit (Choi, 2018; Guo, 2019). Third, research has taken a process perspective (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…role complexity, pressure) that can interfere with individuals’ learning ability. A second, more normative, perspective focuses on the extent to which newcomers learn about what emotions are acceptable in their new organization and how to adjust their own emotions to create a better fit (Choi, 2018; Guo, 2019). Third, research has taken a process perspective (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies showed that employees seek job-relevant resources from organizational insiders [59][60][61][62][63]; the most prominent example of organizational insiders that employee can find are their coworkers. Coworkers provide important job-relevant resources such as information on role demand as well as technical, and normative information; these types of information are beneficial for employees' in-role performance [40,61,64]. When employees have a high degree of job autonomy, they have fewer restrictions in utilizing the job resources that they received from their supervisor in the form of consistent feedback and communication, which are marks of behavioral integrity.…”
Section: Job Autonomy As a Moderatormentioning
confidence: 99%
“…Socialization may entail learning (if only implicitly; Choi, 2018) how to utilize: (1) the framing rules by making sense of given situations – including one’s own and others’ affect – in certain preferred ways (cf. “organizational emotion [affect] scripts”; Gibson, 2008: 277); (2) the feeling and display rules by engaging in emotional labor (i.e.…”
Section: Affective Climate and Culture From The Top Downmentioning
confidence: 99%
“…The two primary means of socialization are formal practices and more informal on-the-job training. Formal practices reflect “institutionalized socialization”, where newcomers are grouped together for training purposes, segregated from other organizational members for a defined period, trained by veterans, follow a fixed sequence of steps and timelines, and are encouraged to adopt an organizationally preferred sense of self (Choi, 2018; Van Maanen and Schein, 1979). Schweingruber and Berns (2005: 681) describe a week-long “emotional training” program (the company’s term) for door-to-door book salespeople.…”
Section: Affective Climate and Culture From The Top Downmentioning
confidence: 99%